2017
DOI: 10.15282/jmes.11.2.2017.16.0250
|View full text |Cite
|
Sign up to set email alerts
|

Thermal phenomenon of glass fibre composite under tensile static and fatigue loading

Abstract: The aim of this study is to understand the thermal phenomenon of unidirectional Glass Fibre Reinforced Polymer (GFRP) composite under static and fatigue (tensile) loads. This study used a rectangular shaped GFRP composite and consisted of specimens with and without a circular notch. Under static test, the constant displacement rate was applied. Under fatigue test, frequency and amplitude of stress were explored to study the fatigue properties and damage evolution of the specimen. Thermography was used in real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As described in [ 28 , 29 , 30 ], the heating of the test specimen can be detected by means of thermographic analyses and considered in connection with the evaluation of viscoelastic effects or damage processes (under progressive load). For example, in [ 26 , 27 , 31 ], the temperature change in a composite material is measured by means of an infrared (IR) camera system and used to define a dimensioning limit for cyclically tensile stressed test specimens. Based on the results of these studies, the test method is validated within the scope of this contribution by means of an IR camera of the type ImageIR 8300 (InfraTec GmbH, Dresden, Germany), which is used to detect the heating of the tensile specimen in the DMTA during the mechanical test ( Figure 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…As described in [ 28 , 29 , 30 ], the heating of the test specimen can be detected by means of thermographic analyses and considered in connection with the evaluation of viscoelastic effects or damage processes (under progressive load). For example, in [ 26 , 27 , 31 ], the temperature change in a composite material is measured by means of an infrared (IR) camera system and used to define a dimensioning limit for cyclically tensile stressed test specimens. Based on the results of these studies, the test method is validated within the scope of this contribution by means of an IR camera of the type ImageIR 8300 (InfraTec GmbH, Dresden, Germany), which is used to detect the heating of the tensile specimen in the DMTA during the mechanical test ( Figure 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the metallic materials case, a lot of scientific researches consider the fatigue damage monitoring by thermal methods in composite materials [11][12][13][14][15][16][17], but only some of these attempt to evaluate the fatigue limit [13,16]. The application of IR-thermography to different glass and basalt fibre-reinforced composite materials, to relate their thermal response to the mechanical behaviour, is presented in [11].…”
Section: Introductionmentioning
confidence: 99%
“…A technique to pass from temperature information to distribution of heat sources on the composites surface to monitor the damage evolution of some carbon/epoxy composite specimens during a fatigue test has been proposed [16]. Only one study analysed the influence of a particular type of notch as a central hole [17] but no study has analysed the presence of notch with different geometries in composites. The aim of this previous study was to understand the damage evolution of unidirectional GFRP specimens with and without a circular notch under static and fatigue loads, by observing the thermal phenomena on the external surface of the GFRP composite [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where, α1 and α2 are the coefficients of thermal expansion (μm/m o C), Cp is the specific heat at constant pressure (J/g o C), ρ is density (g/cc) and Δσ is the change in stress (N/m 2 ) where subscripts 1 and 2 denote the longitudinal and transverse to fibre directions. Furthermore, most research works based on thermography on composite material has shown that thermal analyses can indicate the damage location on the specimen surface and successfully detected the damage formation and propagation based on the temperature evolution under static loading conditions [13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%